Penerapan perilaku pendidikan budaya anti korupsi di Indonesia saat ini - Safira, Sela (Maliki Interdisciplinary Journal, 2024)
The Corruption is still one of the nation’s problems that is difficult to overcome. Corruption is bad behavior, barbaric behavior, human animal behavior that can harm other parties, so the importance of implementing anti-corruption cultural education behavior is very important for a country that aims according to the goals of the Republic of Indonesia as stated in the 1945 Constitution of the Republic of Indonesia. Education plays an important role in this corruption case by instilling an anti-corruption culture from an early age. The researcher researched with qualitative research by observing several literature studies, namely by analyzing various books, articles, journals related to the theme. Furthermore, collecting data using documentation techniques in order to find research data. The author processes the research data using several procedures, including starting with data collection, then processing, and finally verification.